A real options approach to production and injection timing under uncertainty for CO2 sequestration in depleted shale gas reservoirs. (1st April 2020) - Tayari, Farid; Blumsack, Seth
Graphical abstract: Highlights: We investigated the uncertainty of CO2 sequestration in depleted Shale-gas. We solved the profit-maximization for different methane and CO2 price levels. We found CO2 and CH4 price pairs with equivalent injection or production profit. As CO2 price increases, option value and likelihood to delay injection decreases. As the discount rate grows, value of the option drops. Abstract: Depleted shale gas reservoirs may be candidates for conversion to injection wells for the long-term geologic storage of CO2, but the decision to transition from production to injection depends on economic and policy factors that may be uncertain. This paper aims to comprehend the uncertainty inherent to the underlying assumptions of CO2 sequestration and their impact on the injection decision. We view and analyze the production to injection transition decision as a kind of options problem, where the owner of a producing well can choose to exercise the option to stop producing natural gas and start injecting CO2 . Our approach integrates a detailed reservoir model for shale-gas production and CO2 injection in the Marcellus shale formation with a multi-period decision problem under uncertainty in future prices for CO2 and produced natural gas. With no uncertainty, the modeling framework is able to identify the optimal timing of the transition to CO2 injection as a function of natural gas prices and a hypothetical CO2 price. We find that a CO2 price of approximately 15 per tonne to be needed in order to incentivize a producer to transition to CO2 injection earlier. If these prices are uncertain, we find that the option to delay CO2 injection has value even when CO2 prices are relatively high and natural gas prices are low, although the option value is highly sensitive to the choice of discount rate and the option value to delay injection is generally very low when CO2 prices are 20/tonne or higher. Our modeling suggests that commitment in carbon pricing regimes is of equal importance to the choice of the price level.